TEACHING ENGLISH TO YOUNG LEARNERS USING PUPPET: A CASE STUDY IN ONE OF PRIMARY SCHOOLS IN SUMEDANG REGION - Raynesa Noor Emiliasari (Jurnal Educatio, 2015)
Teaching English to young learners has its own challenges, especially in Indonesia where English is categorized as Foreign Language. Teachers of young learners should provide the care necessary to meet young learners’ needs so that they can thrive and focus on their learning (Linse, 2005:2). This study aims to investigate the use of puppet in teaching English at primary school and to seek the teacher’s and students’ respond and enthusiasm toward the use of puppet in teaching English. The research method used in this study was a case study conducted in one of the primary schools in Sumedang region on students whose the L1 is Sundanese. The results of the study reveals that with the puppet media teaching English to young learners become more interesting and enjoyable. The students are more comfortable, enthusiastic and confident in sharing their ideas. The teacher was assissted with the puppet to deliver the material. The study used classroom observation to gather the data related to the teaching-learning process; teacher’s and students’ interview to find out their respond and enthusiasm toward puppet in teaching English. The findings recommended English teachers of young learners to use the puppet in their teaching-learning process. Keywords: teaching english, young learners, puppet.